Potential Hyperglycemia In Type 2 Diabetes Mellitus Patients Due To Drug Interactions At Hospital - Avrillana Dewangi Gea Ayunda Diarso; Shinta Mayasari; Khrisna Agung Cendekiawan (Indonesian Pharmacopeia Journal, 2024)
Background: Hyperglycemia is a medical condition in the form of an increase in blood glucose levels beyond normal limits with a blood sugar concentration of ≥200 mg/dl. Hyperglycemia that is not well controlled can cause serious disorders of the body's systems, especially the nerves and blood vessels. Based on WHO data, the prevalence of type 2 DM with the potential for hyperglycemia in the world in 2019 was 5.3%. This figure is expected to increase to 6.3% in 2030. Objective: This research was conducted to determine the potential for hyperglycemia in type 2 diabetes mellitus patients due to drug interactions at one of hospital in Jember. Method: This research uses a quantitative design with retrospective data collection, namely research obtained based on information from patient medical records. The population in this study was 539 patients suffering from type 2 diabetes mellitus for the period January-December 2022. The sample from this study was type 2 diabetes mellitus patients who met the inclusion criteria. Sampling was calculated using the Slovin formula using random sampling techniques and the results obtained were 84 medical record samples. Analysis using univariate. Data is displayed in frequency and percentage form. Data processing uses Microsoft Excel and SPSS. Results: Most of the drugs received by type 2 diabetes mellitus patients experienced interactions that had the potential to cause hyperglycemia with blood sugar levels ≥200 mg/dl (96.43%) and a moderate clinical significance level of 70.24%. Conclusion: There is a potential for hyperglycemia caused by diabetes drug interactions. Monitoring drug interactions and effective treatment in patients with type 2 diabetes mellitus needs to be carried out to achieve optimal therapy targets and increase awareness of healthy lifestyles in diabetes management.